On the identification of the angular position of gears for the diagnostics of planetary gearboxes. (15th January 2017) - D'Elia, G.; Mucchi, E.; Cocconcelli, M.
Abstract: Generally, in planetary gearbox diagnostics, vibration transducers are placed on the gearbox case near the ring gear. The relative angular position of the planet gears with respect to the transducer is a useful information for the evaluation of vibration signals related to planet/sun gears. This angular position is usually unknown, or it is known with a large tolerance causing serious difficulties in both gears and bearing diagnostics. In fact, noise and spurious component from healthy planets could overhang the informative content about incipient faults. The present work seeks to propose two alternative methods for the identification of the angular position of the planet gears with respect to the transducer. The first one is based on the study of how the power flows inside the Time Synchronous Average of the ring gear, whilst the second method is based on a modified statistical parameter such as the Crest Factor. The effectiveness of these methods is assessed on the basis of actual vibration signals acquired from a faulty planetary gearbox. The knowledge of the exact angular position of the planet gears allows the diagnostics of both gears and bearings, as proven by extensive experimental activities reported in the paper. Abstract : Highlights: The paper focuses on the diagnostics of planetary gearboxes. The paper focuses on the diagnostics of gears and bearings, considered as a whole. The angular position of the planet gears w.r.t the transducer is studied. The experimental activities reported in the paper support the proposed methodology.